Chthonic Legal Traditions towards Emic Understandings of Australian First Nations Constitutionalism: 'Rooted' Constitutionalism and a Foundational Conceptual Apparatus for Inquiries into Australian First Nations Legal Orders - Maria Randazzo (9768773) (2020)
First Nations constitutionalism unfolds within a chthonic legal tradition which is incommensurable with most of the positivist theoretical and conceptual models deployed to investigate Westphalian constitutional systems. The irreducibility of analysis of chthonic constitutional traditions with such models of constitutionalism calls, on the one hand, for rethinking positivistic approaches to legal reasoning and rationalisation and, on the other hand, for identifying new conceptual grids in charting the normative and legal landscape of Indigenous constitutionalism. With specific reference to Australian First Nations constitutionalism, the purpose of this paper is to suggest the adoption of a conceptual apparatus for its investigation which reflects 'emic' understandings of what Indigenous legal orders are and how they operate. In doing so, the paper subsumes Australian First Nations constitutionalism into Mills’s theoretical elaboration of ‘rooted constitutionalism’ and argues that such a ‘rooted’ kind of constitutionalism needs to be expounded through foundational concepts such as nomos , myths, and legal traditions which are experientially and culturally grounded in the lifeworld that sustain Australian First Nations constitutional traditions. Such a conceptual apparatus draws mainly from the theoretical framework elaborated by legal pluralism and legal theory to deal with the contemporary normative complexities of stateless legal orders. It is a macro-level conceptual apparatus that would be foundational to ‘etic’ understanding and theorisation of First Nations Australian constitutionalism.